Mumificação fetal em vacas Nelore - Relato de caso - Moya-Araujo, Carla Fredrichsen [UNESP]; Piagentini, Marcelo [UNESP]; Da Silva, Danilo Cunha [UNESP]; Oba, Eunice; Araujo, Gustavo Henrique Marques (My University, 2016)
Fetal mummification is an abnormal condition in which fetal death occurs after the middle third of pregnancy, when the fetus has occurred ossification and complete resorption in the fetal material cannot be performed. The main complaint of this disease is positive pregnancy diagnosis associated with a prolonged pregnancy. The recommended treatment is the application of prostaglandin for induction of labor or, in cases where the treatment employed was unsuccessful, performing cesarean. In most cases, the prognosis after removal of mummified fetus is good. This article aims to report two cases of fetal mummification in Nellore cows that were answered field, an animal with gestational diagnosis of abuse, whose birth was induced with prostaglandin to 200 days of pregnancy without success and another animal for dystocia.
Fetal mummification in Nelore cows - Case report
Keywords: Gestational disease; Prostaglandin; Zebu cattle